2. Simplify ((–3)2)3

ANSWERS

2015-11-10 03:35:24

We want to simplify ((-3)²)³. Note that (-3)² = (-3)*(-3) = 9. Therefore ((-3)²)³ = (9)³ = 9*9*9 = 729 Answer: 729

2015-11-10 03:36:39

When there are two numbers one to each other, this means that between them there is a multiplying (noted with x or *) So, we can write the equation as: ((-3)*(2))*3. (-3)*(2) is -6 (if one of the multipliers has sign - (is negative) then the product is also negative. If two multipliers are negative, then the product is positive. Now, we have (-6)*3, which gives -18. So the simplified form of ((–3)2)3 is -18.

ADD ANSWER